1985
DOI: 10.1073/pnas.82.22.7716
|View full text |Cite
|
Sign up to set email alerts
|

Experimental diabetic neuropathy: impairment of slow transport with changes in axon cross-sectional area.

Abstract: Analysis of slow axonal transport in the sciatic and primary visual systems of rats with streptozotocininduced diabetes of 4-6 weeks duration showed impairment of the transport of neurofilament subunits, tubulin, actin, and a 30-and a 60-kDa polypeptide in both systems. The degree of impairment was not uniform. Transport of polypeptide constituents of the slow component b, such as the 30-and 60-kDa polypeptides, appeared to be more severely affected than the transport of constituents of the slow component a, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
2
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 52 publications
2
63
2
1
Order By: Relevance
“…Scott et al (33) examined neurofilament and tubulin mRNA expression and demonstrated that a time-dependent decrease in mRNA expression of cytoskeletal proteins in sensory neurons accompanies a reduction in their incorporation into distal axons. These abnormalities build on the observation by Medori et al (34), who demonstrated axonal dwindling secondary to alterations in the axonal transport of structural proteins, with enlargement proximally and atrophy distally.…”
Section: Discussionmentioning
confidence: 99%
“…Scott et al (33) examined neurofilament and tubulin mRNA expression and demonstrated that a time-dependent decrease in mRNA expression of cytoskeletal proteins in sensory neurons accompanies a reduction in their incorporation into distal axons. These abnormalities build on the observation by Medori et al (34), who demonstrated axonal dwindling secondary to alterations in the axonal transport of structural proteins, with enlargement proximally and atrophy distally.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, for >30 years axon transport abnormalities were recognized to have a role in PN caused by DM. 19 DM may lead to alterations in cytoskeletal components, such as actin, neurofilament, and tubulin that are essential for normal intracellular (axon) transport, either by direct glycation in the context of hyperglycemia or as a consequence of impaired gene expression. 20e23 For example, tubulin glycosylation in DM impairs polymerization and alters microtubule dynamics which is essential for trafficking intracellular macromolecules and organelles 24 along microtubule networks.…”
Section: Axon Transport and Its Role In Neuron And Axon Homeostasismentioning
confidence: 99%
“…In agreement with this, multiple abnormalities of NF biology were identified in models of diabetes. An impairment of the axonal transport of NFs, actin and tubulin concomitant with a proximal increase and a distal decrease of axonal calibers were observed in rats with streptozotocin-induced diabetes and in BioBreeding rats (a model of spontaneous type I diabetes) [131,132]. The distal axonal atrophy is accompanied by a concomitant NF loss in this region [133], and accumulations of highly phosphorylated NF epitopes are present in proximal axonal segments of dorsal root ganglia sensory neurons from diabetic patients [134].…”
Section: Diabetic Neuropathymentioning
confidence: 99%